Analysis of Team Member Evaluations Based on Gender. (September 2022) - Tchupo, Dominique Engome; Macht, Gretchen A.
Using data collected from multiple teams of undergraduate engineering students, this study examines whether team members evaluate members of different perceived genders differently than they would a member of their own perceived gender. This was done using social relations modeling to analyze the dyadic differences within the teams over the course of several years. This research found that despite what was expected, gender only played a minor role in how different team members rated each other as time progressed. This lack of significance of gender in the model could be attributed to the high proportion of women in this major as well as how the teams were formed.